ANALISIS KEGAGALAN DAN EVALUASI SISA UMUR REHEATER TUBE KETEL UAP DITINJAU DARI ASPEK PERUBAHAN KETEBALAN DAN CREEP - , NOVI SUKMA DRASTIAWATI, Ir. R. Soekrisno, MSME, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Boilerâs function is very important, as a place to change water phase from liquid to vapor in electric generator of power plant. Variables of process that not appropriate with the standard causes failure. Failure in the re-heater tube is rupture. At tube failure there scale adhere on the outer surface and occurs progressively thinning thickness with a minimum thickness of tube rupture at the nearest corner. The failure resulted in operating losses and stop the transfer of electrical energy to the consumer. In this research analysis to find the cause and determine the failure mechanism and to evaluate the remaining useful life base on thickness changes and creep aspects. Physical analysis were through visual observation of changes in the dimensions and appearance of tube failure. Micro analysis observations in the form of micro-crystal grain shape and presence or absence of a fissure through the crystal grain boundaries. Mechanical properties analysis were done by hardness, tensile, and impact test. Chemical composition analysis were done at the scale product that adhered on the outer surface tube, new tube, and tube failure. Another analysis conducted by corrosion test. Lifetime evaluation were done by testing the remaining life of creep and stress rupture were analyzed using Larson-Miller equation. Base on the results of analysis and data that achieved, failure were caused by oxidation and corrosion reactions of sulfur as a product of incomplete combustion react with hydrogen to form H2S which is a trigger to accelerate the corrosion process for the thinning at the outer surface tube. The results of the micro analysis observations indicate tube has intergranular creep fracture as indicated by the presence of a fissure through the grain boundaries. Another factor supporting of a failure is the presence of scale attached to the outer surface of the causes differences in the distribution of temperature between the outer surface to the inner surface so that the tube is plastically deformed. On the outer surface has a lower temperature and high hardness value is easier to deform the tube so that the tube thickness were decreased due to the corrosion process, the remaining area did not though to hold up the pressure from inner tube until rupture. The results of the analysis of the remaining life evaluation found that at temperatures of 6000C with a thickness of 3 mm about 16 years without any safety factor and about 10 years with a safety factor. At a thickness of 1.364 mm in the remaining life of the tube obtained about 6 years with no safety factor and is about 2 years with a safety factor.